If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 6 = x + 15 Reorder the terms: 6 + X = x + 15 Reorder the terms: 6 + X = 15 + x Solving 6 + X = 15 + x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + X = 15 + -6 + x Combine like terms: 6 + -6 = 0 0 + X = 15 + -6 + x X = 15 + -6 + x Combine like terms: 15 + -6 = 9 X = 9 + x Simplifying X = 9 + x
| x(x+7)=73 | | 23-16n=-1 | | 3m2/8=6 | | -7(6x+5)=-7x+14 | | 0=00m | | 1,340,000,000,000i=23 | | -15=-1.5m | | (2x-4y+6)dx=(3-x-y)dy | | 3tan^2x+4=5 | | (6)(3i+4)(1)+(4y+1)(2i)=(8iy+2i)+(18i+24) | | 19x+13y=7 | | -8x+4y=-12 | | 15-d=8 | | 0.045x-5/8y=120 | | x^8-26x+25=0 | | 2x+14i=1 | | (x^3+3x^2-16x-48)=0 | | -37+46.98-(-0.02)= | | 5s-(100+2s)=0 | | 3(10-6)(3-7)= | | 55m-139m-64m= | | 8x^6/6x^3 | | ln(x-3)=1.4 | | x-9(2/3x-6)=30 | | 1/2z=9/4 | | -5/13x=-8 | | 5m-139m-64m= | | 10m^3n^3-2mn^2+14mn= | | x+y-3z=-7 | | -9+8x=7x+15 | | 5(x+8)-6=44 | | 8x^2-28x+2x-7=.5 |